DEVELOPMENT OF EDUCATION IN THE CONTEXT OF THE MAIN CHALLENGES OF GLOBALIZATION - Ivan Syladiy ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The world experience of civilizational development of the most advanced countries of the world testifies to the crucial role of the educational sphere in the formation of the whole sociocultural complex - modernization of production, improvement of social relations, science and culture, ensuring sustainable development of society, entry of industrial countries into the stage of post-industrial information society. Educational systems have always focused on the needs of society and, despite the known conservatism, responded to the changes. The concept of "globalization of education" means the process of entry of the educational system into the European Higher Education Area and standardization of requirements: comparability of degrees, a single system of credit points, academic mobility and assessment of the quality of education. The globalized world is an open world, but not an equal one. New challenges in the system of human preparation for life are not least due to socio-cultural dynamics, which is constantly accelerating under the pressure of globalization and the information revolution. Therefore, today it is important to know the main vectors of globalization and informatization not only on the development of modern society in general but also on the development of its education system in particular. The social stratification of states deepens faster than material, financial, intellectual, human resources and talents are pumped out of backward countries.